Assessing the Impact of CRM on Customer Loyalty Through Linear Regression Analysis - Harahap, Diana Sari; Agustalinda Nora; Fithra Maharani (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study aims to determine the effect of Customer Relationship Management (CRM) on customer loyalty at PT Bank Mandiri (Persero) Tbk Padangsidimpuan Branch. The research method used is quantitative, with a data collection approach through observation, questionnaires, interviews, and documentation studies. Data analysis was carried out using simple linear regression techniques, hypothesis testing (t test), and the coefficient of determination (R²) test. The results showed that the regression coefficient value was +0.509, which indicated a positive relationship between CRM and customer loyalty. Hypothesis test analysis produces at value of +6.364 with a significance level of 0.000, which is smaller than 0.05. This shows that CRM has a positive and significant effect on customer loyalty partially. Based on the coefficient of determination analysis, the R² value of 43.9% indicates that CRM is able to explain 43.9% of customer loyalty variability, while the remaining 56.1% is influenced by other factors not discussed in this study. Thus, this study concludes that Customer Relationship Management has a significant influence on customer loyalty at PT Bank Mandiri (Persero) Tbk Padangsidimpuan Branch. These results strengthen the hypothesis that CRM is an important factor in building and increasing customer loyalty.